The Clinical Spectrum of ANO3—Report of a New Family and Literature Review - Percetti, Marco; Zini, Michela; Soliveri, Paola; Cogiamanian, Filippo; Ferrara, Mariarosa; Orunesu, Eva; Ranghetti, Alessandra; Ferrarese, Carlo; Pezzoli, Gianni; Garavaglia, Barbara; Isaias, Ioannis Ugo; Sacilotto, Giorgio (Movement disorders clinical practice (Hoboken, N.J.), 2024)
Background Mutations in ANO3 are a rare cause of autosomal dominant isolated or combined dystonia, mainly presenting in adulthood. Cases We extensively characterize a new, large ANO3 family with six affected carriers. The proband is a young girl who had suffered from tremor and painful dystonic movements in her right arm since the age of 11 years. She later developed a diffuse dystonic tremor and mild extrapyramidal signs (ie, rigidity and hypodiadochokinesis) in her right arm. She also suffered from psychomotor delay and learning difficulties. Repeated structural and functional neuroimaging were unremarkable. A dystonic tremor was also present in her two sisters. Her paternal aunt, father, and a third older sister presented episodic postural tremor in the arms. The father and one sister also presented learning difficulties. The heterozygous p.G6V variant in ANO3 was identified in all affected subjects. Literature review Stratification by age at onset divided ANO3 cases into two major groups, where younger patients displayed a more severe phenotype, probably due to variants near the scrambling domain. Conclusions We describe the phenotype of a new ANO3 family and highlight the need for functional studies to explore the impact of ANO3 variants on its phospholipid scrambling activity.